Design And Application Scheduling Foundation Course In STIKES RS. Dr. Soetomo Surabaya - Suhalim, Wardah Lucianna; Sulistiowati, Sulistiowati; Lementara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
STIKES Foundation. Dr. Soetomo Hospital is a private university owned by the Foundation Dr. SoetomoÂ  Hospital. Making a schedule of courses takes a long time is approximately 28 days. Scheduling courses still use Microsoft Excel application crashes that often occur between the rooms were used and then giving the information is still informed by the bulletin board so students should see the information board for any changes in scheduling courses. Based on description above, then made a system that can help accelerate the creation of appropriate teaching faculty schedule availability of teaching and scheduling criteria that lecturers are not scheduled to teach more than one course at the same time and room at the same time. To make scheduling lecturers teaching methods make use of Genetic Algorithms (coding scheme, and chromosomes initial population, fitness function, selection, crossover, mutation and elitism). With the application of scheduling courses can help accelerate the schedule of lecturers to teach in accordance with the terms and criteria. Teaching faculty scheduling application can simplify the manufacture of useful reports to provide information to the head of Prodi.